Developing Coffee Tourism in Indonesia: A Bibliometric Analysis - Octaviany, Vany; Utami, Dwiesty Dyah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Coffee tourism is becoming an increasingly important component of the travel market niche due to the global expansion in coffee production, consumption, and the coffee industry. This is because only a tiny segment of the population—coffee lovers—will see value in coffee as a stand-alone commodity. Indonesia is the world's largest producer of coffee, so it has the potential to grow its coffee tourism industry. Indonesia must strengthen its coffee tourism industry to combine tourism and coffee as commodities. Regarding the growth of coffee tourism in Indonesia, bibliometric analytic techniques have not yet been investigated in any studies. As a result, this topic requires research into bibliometric analytical methods. This study uses the technique of bibliometric analysis, which is used to evaluate bibliographic data found in articles or journals, to classify, measure, and analyze information found in articles such as titles, authors, keywords, research methodological approaches, data collection, and research results, and to learn more about the extent of academic research on the growth of coffee tourism in Indonesia. Studies on tourism development, coffee tourism, and Indonesia included topic areas with titles, keywords, and abstract requirements. According to the study's findings, Indonesia saw a fluctuating number of articles from 2012 to 2022 about tourism and coffee tourism growth. Elsevier was the publisher that produced the most publications on this subject, and according to the number of citations, Elsevier had the most citations overall. Then, it was discovered that P. Kuswarini was the most productive writer among the authors of essays on these two subjects. The study utilizing VOSviewers' findings demonstrates the connections between the subjects covered.